Is locally advanced head and neck cancer 'increasing' in the Netherlands? The paradox of absolute numbers, standardized incidence rates and proportional share. (March 2023) - van Beers, M.A.; Schreuder, W.H.; Balm, A.J.M.; van Dijk, B.A.C.
Highlights: Locally advanced head and neck cancer is defined in various ways. Netherlands Cancer Registry data show an increase of locally advanced oral and oropharynx cancer. Standardized rates of locally advanced hypopharynx and larynx cancer have declined recent years. The proportionate share of locally advanced larynx cancer has increased. There is an urgent need for standardization of the definition locally advanced head and neck cancer. Abstract: Background: Several reports have indicated that locally advanced head and neck cancer (LAHNC) has increased in the past decade. However, incidence trends cannot be easily compared because slightly different definitions of LAHNC were used. Aim: To investigate if the incidence of locally advanced disease (LAD) in the oral cavity, oropharynx, hypopharynx and larynx is indeed increasing over time, considering the growing and ageing population in the Netherlands. Patients and methods: Data were obtained from the Netherlands Cancer Registry (NCR). Primary head and neck squamous cell carcinomas of the oral cavity, oropharynx, hypopharynx and larynx diagnosed between 1989 and 2017 were included. Yearly numbers and European standardized incidence rates (ESRs) were reported by extent of disease. The annual percentage change (APC) over time in ESRs was calculated to assess trends. Results: Absolute numbers and ESRs of LAD increased over time for oral cavity and most prominently for oropharynx carcinomas (before 1996, APC: 0.4, 95%CI: 0.1; 0.8 and APC: 5.7 (95%CI: 3.1; 8.4) after 1996: 1.5 (1.0; 2.0) respectively. For hypopharynx cancer the absolute number and ESR of LAD increased until 1997 and declined with 0.8% per year since 1997. Absolute numbers of patients with larynx cancer stayed stable over time, while ESR decreased (APC: −0.8 (95%CI: −1.1; −0.6)). Conclusion: The perception of an increasing trend in LAD in the Netherlands can be attributed to the increasing incidence of oral cavity and oropharynx carcinomas. For LAD of the hypopharynx a decreasing trend was observed. In larynx cancer, the proportional share of LAD of the larynx increased, even though incidence rates declined.